Adiwiyata Program Governance Based on Green Theology in Strengthening Environmental Awareness Culture - Septian Nur Ika Trisnawati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The environmental crisis urges educational institutions to foster a culture of environmental awareness through programs that are not merely technical but also institutionalized within school governance. In Indonesia, the Adiwiyata Program was developed as a strategic policy to promote environmentally friendly schools through educational, participatory, and sustainable principles. The Adiwiyata Program has been promoted as a national strategy to develop environmentally friendly schools; however, its implementation often faces challenges such as weak coordination, limited resources, and insufficient internalization of values as drivers of school culture. This study aims to analyze the governance of the Adiwiyata Program based on Green Theology in strengthening environmental awareness culture in madrasah. Employing a qualitative approach with a case study design, the study involved a school principal, two Islamic Education teachers, and five students selected through purposive sampling. Data were collected through in-depth interviews, observations, and document analysis, and analyzed using the interactive model of Miles and Huberman supported by source and method triangulation. The findings indicate that program governance is strengthened through the articulation of a religious–ecological vision as a policy framework, the establishment of program management structures through the Adiwiyata Team and Waste Working Group, the implementation of routine programs integrated into learning activities, and the reinforcement of school culture through habituation, role modeling, and symbolic communication. The main challenges include limited waste sorting facilities and uneven internalization of Green Theology values among students. This study proposes the Green Theology in Practice model as a conceptual contribution to value-based school governance that can be replicated to strengthen the institutionalization of sustainable green school culture.